Applications of Fluorous Porphyrinoids: An Update. (19th August 2021) - Aggarwal, Amit; Bhupathiraju, N. V. S. Dinesh K.; Farley, Christopher; Singh, Sunaina
Abstract: Porphyrins and related macrocycles have been studied broadly for their applications in medicine and materials because of their tunable physicochemical, optoelectronic and magnetic properties. In this review article, we focused on the applications of fluorinated porphyrinoids and their supramolecular systems and summarized the reports published on these chromophores in the past 5‐6 years. The commercially available fluorinated porphyrinoids: meso‐perfluorophenylporphyrin (TPPF20 ) perfluorophthalocyanine (PcF16 ) and meso‐perfluorophenylcorrole (CorF15 ) have increased photo and oxidative stability due to the presence of fluoro groups. Because of their tunable properties and robustness toward oxidative damage these porphyrinoid‐based chromophores continue to gain attention of researchers developing advanced functional materials for applications such as sensors, photonic devices, component for solar cells, biomedical imaging, theranostics and catalysts. Abstract : This review focuses on the recent advances in the chemistry of fluorous porphyrinoids and their hybrid supramolecular systems for applications such as catalyst, photonic devices, sensors and therapeutics.